Identification of metabolic changes leading to cancer susceptibility in Fanconi anemia cells. (10th April 2021) - Abad, Etna; Samino, Sara; Grodzicki, Robert L.; Pagano, Giovanni; Trifuoggi, Marco; Graifer, Dmitry; Potesil, David; Zdrahal, Zbynek; Yanes, Oscar; Lyakhovich, Alex
Abstract: Fanconi anemia (FA) is a chromosomal instability disorder of bone marrow associated with aplastic anemia, congenital abnormalities and a high risk of malignancies. The identification of more than two dozen FA genes has revealed a plethora of interacting proteins that are mainly involved in repair of DNA interstrand crosslinks (ICLs). Other important findings associated with FA are inflammation, oxidative stress response, mitochondrial dysfunction and mitophagy. In this work, we performed quantitative proteomic and metabolomic analyses on defective FA cells and identified a number of metabolic abnormalities associated with cancer. In particular, an increased de novo purine biosynthesis, a high concentration of fumarate, and an accumulation of purinosomal clusters were found. This was in parallel with decreased OXPHOS and altered glycolysis. On the whole, our results indicate an association between the need for nitrogenous bases upon impaired DDR in FA cells with a subsequent increase in purine metabolism and a potential role in oncogenesis. Highlights: Apart from DNA repair, Fanconi anemia (FA) genes contribute to cellular metabolism. De novo purine biosynthesis, fumarate level and glycolysis are upregulated in FA cells. New insights into the FA network in connection to metabolic pathways are provided.